RANCANG BANGUN SCORING BOARD MENGGUNAKAN SMS (SHORT MESSAGE SERVICE) BERBASIS MIKROKONTROLER ATMEGA 32 - ., Zeky Leo Karza (Jurnal Teknik Elektro Universitas Tanjungpura, 2013)
Abstrack: Scoring Board via SMS is a microcontroller-based system that can be used to provide information about the results of football matches, both scor match results and team names that match. To input the name of the team in the scoring system board must send a sms with a given format ie "A team name and team name B". There are other commands with different command functions also vary. Conditioned system created by the network provider Telkomsel, as well as mobile phones used in the system is the Siemens C45 mobile phone. Unit controller used in the scoring system board is ATMEGA32. Keywords : scoring board, mikrokontroller ATmega32, Siemens C45, sevent segment.